Second-line therapy of squamous non-small cell lung cancer: an evolving landscape. (3rd June 2017) - Lazzari, Chiara; Karachaliou, Niki; Gregorc, Vanesa; Bulotta, Alessandra; Gonzalez-Cao, Maria; Verlicchi, Alberto; Altavilla, Giuseppe; Rosell, Rafael; Santarpia, Mariacarmela
ABSTRACT: Introduction : The treatment of lung cancer has radically changed over the last few years. The discovery of druggable oncogenic alterations and the introduction of immunotherapy have provided lung cancer patients with the possibility of more efficient and less toxic therapeutic alternatives than chemotherapy. In the case of lung squamous cell carcinoma (LSCC), the treatment progress is slower than adenocarcinoma, for which several targeted agents have been already approved. The standard first-line therapy for LSCC, in most sites of the world, is platinum-based chemotherapy. After disease progression, these patients now have novel treatment options, including antiangiogenic agents and immune checkpoint blockade. Areas covered : We provide a summary of the recent novelties for the second-line therapy of LSCC, emphasizing on the results of the most important clinical trials that have led to regulatory approvals. Expert commentary : Immune checkpoint inhibitors have changed the therapeutic algorithm for LSCC patients. Other treatment options in the second-line setting include ramucirumab in combination with docetaxel and afatinib. However, we still lack biomarkers to predict which patients could respond better to each treatment. Despite the identification of several actionable molecular alterations, there are no approved targeted agents specific for advanced LSCC. Results from ongoing biomarker-driven studies are eagerly awaited to establish effective treatments for molecularly selected subgroups of patients.